Noticing cigarette health warnings and support for new health warnings among non-smokers in China: findings from the International Tobacco Control project (ITC) China survey - Zejun Li; Tara Elton-Marshall; Geoffrey T. Fong; Anne Chiew Kin Quah; Guoze Feng; Yuan Jiang; Sara C. Hitchman (BMC, 2017)
Abstract Background Health warnings labels (HWLs) have the potential to effectively communicate the health risks of smoking to smokers and non-smokers, and encourage smokers to quit. This study sought to examine whether non-smokers in China notice the current text-only HWLs and whether they support adding more health information and including pictures on HWLs. Methods Adult non-smokers (n = 1324) were drawn from Wave 4 (September 2011-November 2012) of the International Tobacco Control (ITC) China Survey. The proportion of non-smokers who noticed the HWLs, and supported adding more health information and pictures to the HWLs was examined. Additionally, the relation between non-smokers' demographic characteristics, including whether they had a smoking partner, their number of smoking friends, and noticing the HWLs and support for adding health information and pictures was examined. Because the HWLs changed during the survey period (April 2012), differences between non-smokers who completed the survey before and after the change were examined. Results 12.2% reported they noticed the HWLs often in the last month. The multivariate model, adjusting for demographics showed that respondents with a smoking partner (OR = 2.41, 95% CI 1.42-4.13, p = 0.001) noticed the HWLs more often. 64.8% of respondents agreed that the HWLs should have more information, and 80.2% supported including pictures. The multivariate model showed that non-smokers who completed the survey after the HWLs were implemented (OR = 0.63, 95% CI 0.40-0.99, p = 0.04) were less likely to support adding more health information. The multivariate model showed a significant relation between having a smoking partner and supporting pictorial HWLs (OR = 2.03, 95% CI 1.24-3.33, p = 0.005). Conclusions The findings indicate that the Chinese HWLs are noticed by a minority of non-smokers and that non-smokers strongly support strengthening the Chinese warning labels with more health information and pictures. Additionally, because the HWLs are noticed more often by non-smokers with a smoking spouse/partner, HWLs could be used to communicate the dangers of smoking and secondhand smoke exposure to non-smokers.